Autonomous orbit determination using observations of a sodium guide‐star network. Issue 2 (29th April 2019) - Psiaki, Mark L.; Flewelling, Brien; Hackett, Shawn
Abstract: A new method of spacecraft orbit determination is developed based on position information from the observation of fluorescing streaks in the atomic sodium of Earth's upper atmosphere. This concept could be used for GPS constellation autonomous navigation (AutoNav). This new orbit determination method uses a spacecraft‐mounted camera to observe fluorescing line segments in the sodium layer. The fluorescence is excited by ground‐based sodium guide‐star lasers. The system also uses a star tracker in order to reference the measured guide‐star directions to inertial coordinates. The measured direction to an unknown point on a known guide‐star segment at a known time defines a plane on which the spacecraft must lie. Seven or more independent measurements suffice to determine a Keplerian orbit and the spacecraft clock offset. Cramer‐Rao analysis indicates that 1 − σ position accuracies on the order of 20 m or better may be achievable for filtering intervals of several days.